2016
DOI: 10.1002/smi.2728
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in response to chronic terrorism threats: A construct of emotional, cognitive, and behavioral responses among Israeli citizens

Abstract: Israeli citizens are exposed to unpredictable and chronic terrorism threats that significantly jeopardize their personal sense of safety. The purpose of the present study is to present how Israeli discourse is structured with regard to emotional, cognitive, and behavioral responses to chronic terrorism threats and to understand the range of responses as well as map the risk and protective factors of this existential threat. Semistructured in-depth interviews were conducted with 40 Israeli adults (22 women and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Those studies compared two waves of the pandemic and indicated that PTG increased from one wave to the next ( Feingold et al, 2022 ). These findings are in line with the general research on continuous traumatic/stressors situations, indicating that the effects of exposure to ongoing mass traumas such as terrorism are positively associated with positive outcomes and PTG ( Laufer and Solomon, 2006 ; Cohen-Louck and Saka, 2017 ). When coping with continuous uncertainty and existential threats, people tend to engage in psychological processes that facilitate a sense of coherence and understanding of these continuous adversities ( Veronese et al, 2017 ).…”
Section: Introductionsupporting
confidence: 90%
“…Those studies compared two waves of the pandemic and indicated that PTG increased from one wave to the next ( Feingold et al, 2022 ). These findings are in line with the general research on continuous traumatic/stressors situations, indicating that the effects of exposure to ongoing mass traumas such as terrorism are positively associated with positive outcomes and PTG ( Laufer and Solomon, 2006 ; Cohen-Louck and Saka, 2017 ). When coping with continuous uncertainty and existential threats, people tend to engage in psychological processes that facilitate a sense of coherence and understanding of these continuous adversities ( Veronese et al, 2017 ).…”
Section: Introductionsupporting
confidence: 90%
“…Believing in an omnipotent God affords an all-encompassing view of reality that explains reality and enables people to believe that they can control their surroundings (including uncontrollable events) by currying favor with beings more powerful than themselves who can do things they themselves cannot (Vail et al, 2010). Especially in uncontrollable situations such as terrorism, people turn to the one whom they perceive as having control (Cohen-Louck & Saka, 2017; Solomon & Berger, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Coping with chronic political violence may be different in a few respects. For one, chronic political violence is somewhat more predictable than a one-off terror event ( Cohen-Louck & Levy, 2020 ), may result in habituation over time ( Cohen-Louck & Saka, 2017 ), and may thus be associated with lower use of coping strategies ( Cohen-Louck & Ben-David, 2017 ), at least for some individuals. Normalization of living under continuous political violence may be more plausible for emotionally stable individuals, whereas neurotic ones may become even less balanced than usual and continue their unsuccessful efforts to cope.…”
Section: Discussionmentioning
confidence: 99%